High‐Performance Olivine for Lithium Batteries: Effects of Ni/Co Doping on the Properties of LiFeαNiβCoγPO4 Cathodes. (20th May 2015) - Pagot, Gioele; Bertasi, Federico; Nawn, Graeme; Negro, Enrico; Carraro, Giorgio; Barreca, Davide; Maccato, Chiara; Polizzi, Stefano; Di Noto, Vito
<x xml:space="preserve">Abstract</x> New high voltage and high capacity storage systems are needed to sustain the increasing energy demand set by the portable electronics and automotive fields. Due to their good electrochemical performance, lithium‐transition metal‐phosphates (LiMPO4) seem to be very attractive as cathode materials for lithium secondary batteries. Here the synthesis and the characterization of five high voltage cathodes for lithium batteries, based on lithium–iron, lithium–nickel, lithium–cobalt phosphates are described. The effect of differing degrees of cobalt and nickel doping on structure, morphology, and the electrochemical properties of the different materials is thoroughly studied. Transition metal atoms in these materials are found to be vicariant within the olivine crystal structure; however, the lattice parameters and cell volume can be modulated by varying the nickel/cobalt ratio during the synthesis. High performance battery prototypes in terms of voltage (>4.0 V), specific capacity (125 mAh g−1), specific energy (560 mWh g−1), and cyclic life (>150 cycles) are also demonstrated.